Help to deal with trauma - Ng, Alvin Lai Oon * (Star Media Group Berhad, 2023)
I REFER to the report, “Two Orang Asli survivors still in shock eight years on” (The Star, July 26). The report highlights how systemic stressors such as delays in payout of welfare funds to the victims as well as technological and geographical barriers to counselling prolong their distress and trauma.